2019
DOI: 10.3901/jme.2019.08.097
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High Temperature on Thermal Fatigue Crack Initiation Life of Automotive Gray Cast Iron Brake Disc

Abstract: :The brake disc of a vehicle often works at high temperature, and its damage caused by thermal fatigue easily takes place. So the performance of the vehicle brake disc is directly related to the safety of driving, and it is very necessary to study the thermal fatigue crack initiation life of the brake disc at high temperature. The monotonic tensile and compressive tests of gray cast iron HT200 sample for vehicle brake discs are carried out at 500 ℃, and the stress-strain curves are analyzed to obtain mechanica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 1 publication
0
2
0
Order By: Relevance
“…Due to high temperatures and heat shock, various cracks can occur on the brake disc's friction surface [41]. The publication [42] has concluded that thermal stress on the brake disc while braking is substantially higher than mechanical stress. Gradually, these cracks expand, and thus, while braking, the brake disc may crack [43].…”
Section: Introductionmentioning
confidence: 99%
“…Due to high temperatures and heat shock, various cracks can occur on the brake disc's friction surface [41]. The publication [42] has concluded that thermal stress on the brake disc while braking is substantially higher than mechanical stress. Gradually, these cracks expand, and thus, while braking, the brake disc may crack [43].…”
Section: Introductionmentioning
confidence: 99%
“…e thermal stress changes repeatedly with the rapid and repeated temperature changes, resulting in fatigue damage to the material. e thermal stress cycle caused by the temperature gradient is a major cause of fatigue failure of the thermowell [4][5][6]. Mudhaffar et al [7] researched the bending behavior of an advanced functionally graded ceramic-metal plate resting on a viscoelastic foundation and subjected to a hygro-thermo-mechanical load; both linear and nonlinear influences of temperature on the bending response were investigated.…”
Section: Introductionmentioning
confidence: 99%